PERAN LINGKUNGAN TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI DESA SEMAMPIR, KRAKSAAN, PROBOLINGGO - Debby Adelita Febrianti Purnamasari; Endah Tri Wisudaningsih (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
Good or bad experiences that children get can occur because of the surrounding environment. Agood environment will also provide good experiences for children. Conversely, if theenvironmental conditions around the child are not good, the experience the child gets will beless good. The aim of this study is to first identify the environment around children, namely thehome and preschool environment. The second, to identify the child's social emotionaldevelopment. The third, to identify the role of the environment for children's social emotionaldevelopment. The approach used in this research is qualitative phenomenology. The survey wascarried out on the environment and experiences of the child. The result of this research is thatthe environment around the child, such as the family environment and the school environment,has an important role in the social emotional development of children. A good familyenvironment and a conducive school environment can create children with good socialemotional development. An unfavorable environment and a less conducive school environmentcan create children with poor social emotional development as well.Keywords: Environment, Social Emotional Development